2016
DOI: 10.1073/pnas.1517066113
|View full text |Cite
|
Sign up to set email alerts
|

Function and regulation of TRPP2 ion channel revealed by a gain-of-function mutant

Abstract: Mutations in polycystin-1 and transient receptor potential polycystin 2 (TRPP2) account for almost all clinically identified cases of autosomal dominant polycystic kidney disease (ADPKD), one of the most common human genetic diseases. TRPP2 functions as a cation channel in its homomeric complex and in the TRPP2/ polycystin-1 receptor/ion channel complex. The activation mechanism of TRPP2 is unknown, which significantly limits the study of its function and regulation. Here, we generated a constitutively active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 93 publications
10
65
0
Order By: Relevance
“…Electrophysiology studies have suggested that heterologous PKD2 currents can be measured from the plasma membrane when it is either expressed with PKD1 in mammalian cells or when mutated (F604P) to render it constitutively active in Xenopus laevis oocytes (Arif Pavel et al, 2016; Hanaoka et al, 2000). However, we find that currents from transfected HEK293T and CHO cells were not different from untransfected cells when measured under physiological calcium or divalent-free sodium conditions (Figures S4A and S4B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrophysiology studies have suggested that heterologous PKD2 currents can be measured from the plasma membrane when it is either expressed with PKD1 in mammalian cells or when mutated (F604P) to render it constitutively active in Xenopus laevis oocytes (Arif Pavel et al, 2016; Hanaoka et al, 2000). However, we find that currents from transfected HEK293T and CHO cells were not different from untransfected cells when measured under physiological calcium or divalent-free sodium conditions (Figures S4A and S4B).…”
Section: Resultsmentioning
confidence: 99%
“…Percent change of the outward current was determined by the following equation: % Change I out = (I drug -I control /I control ) × 100 where I control is the average current measured during the 30 s prior to drug application and I drug is the average current after 60–120 s of drug application. The human PKD2 F604P mutant (Arif Pavel et al, 2016) was recorded in DVF symmetrical 140 mM Na + conditions. Non-transfected HEK293T cells exhibit small outwardly rectifying currents in physiological calcium conditions, which become larger and ohmic (linear) in divalent free conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results contrast with reports that heterologous PKD2 (PKD1 + PKD2) is selective for calcium. The proposed location of F604 is in the fifth transmembrane helix of PKD2, and thus, the activating F604P mutation may create a bend in the activation gate, opening the pore and activating the channel (Arif Pavel et al, 2016). Given the lack of function of WT PKD2, these data suggest a significant conformational change must occur for the channel to open as supported by recent structural studies (Shen et al, 2016).…”
Section: Polycystic Kidney Disease Proteinsmentioning
confidence: 99%
“…Most other cases of ADPKD (70%) are caused by mutations in PC1, which forms a 1:3 complex with PC2 by replacing one PC2 subunit in the channel region (Su et al, 2018a). Phenotypically, ADPKD is characterized by formation of fluid-filled renal cysts, which leads to progressive cystic enlargement in both kidneys and ultimately kidney failure (Pavel et al, 2016). Cysts or diverticula also frequently develop in intestines, liver and pancreas (Wilson, 2004).…”
mentioning
confidence: 99%